Effects of Magnetohydrodynamic on Stagnation Point Flow Past a Stretching Sheet in Presence of Thermal Radiation with Newtonian Heating - Mohd Zuki, Salleh; Muhammad Khairul Anuar, Mohamed; Anwar, Muhammad Imran; Shafie, Sharidan; Anuar, Ishak (Springer, 2013)
In this study, the effects of magnetohydrodynamic on stagnation point flow past a stretching surface in presence of thermal radiation generated by Newtonian heating are studied, where the heat transfer rate from the bounding surface with a finite heat capacity is proportional to the local surface temperature. The transformed boundary layer equations are solved numerically using the Keller-box method. Numerical solutions are obtained for the local heat transfer coefficient, the surface temperature as well as the velocity and temperature profiles. The features of the flow and heat transfer characteristics for various values of the Prandtl number, stretching parameter, magnetic parameter, thermal radiation parameter and conjugate parameter are analyzed and discussed. In conclusion, the thermal boundary layer thickness depends strongly on these five parameters. It is found that, as Prandtl number, stretching parameter and thermal radiation parameter increases, the temperature profiles decreases. While, as magnetic parameter and conjugate parameter decreases, the temperature profiles also decreases.